Art Therapy in Burn Cases: A Review and Case Examples. (April 2022) - Malhotra, Bani; Anand, Susan A.; Kaimal, Girija
Abstract: In this article, we provide an overview of the literature on contributions of art making and medical art therapy for patients with burn injuries. The potential value of art therapy in addressing the complex physical and psychosocial needs of burn patients is discussed through examination of 7 peer-reviewed articles. Two case examples of burn survivors, 1 pediatric and 1 adult, are included to demonstrate the use of art therapy in an inpatient and outpatient setting, respectively. Art therapy and other intervention strategies for overall psychosocial adjustment of burn patients are often underutilized. Further research in art therapy is needed to examine the psychosocial aspects of burns patients and the potential role that medical art therapy may have in a burn care center.